Aplicação da análise envoltória de dados (DEA) na avaliação da eficiência de ações gerenciais para redução de desperdício em obras de construção civil - Barreto, Aerson Moreira (2010)
Production construction management is characterized by decision making in different areas that open from production strategy to site control, going through conceptual design management, design for production, production system planning, long, medium and short term planning. This research work takes the view that the above managerial areas have different impacts on waste generation on building site. In order to develop this idea a study was conducted on 31 building sites. Managerial actions were investigated using a questionnaire survey based on 16 possible areas of site decision taking, that encompass the range of possible managerial actions covered by literature. A Data Envelopement Analisys (DEA) linear programming was applied to identify that are better connected to site wastage efficiency. It concludes that concentration on production strategy, executive design and production control management are the most frequently areas associated with wastage efficiency, while medium and short range planning and PSP are the last important areas according to results obtain from this group building companies